2015
DOI: 10.1016/j.bbadis.2014.07.028
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between autophagy and the ubiquitin–proteasome system in cardiac proteotoxicity

Abstract: Proteotoxicity refers to the detrimental effects of damaged/misfolded proteins on the cell. Cardiac muscle is particularly susceptible to proteotoxicity because sustained and severe proteotoxic stress leads to cell death and cardiac muscle has very limited self-renewal capacity. The ubiquitin-proteasome system (UPS) and the autophagic-lysosomal pathway (ALP) are two major pathways responsible for degradation of most cellular proteins. Alterations of UPS and ALP functions are associated with the accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 91 publications
2
82
0
Order By: Relevance
“…In contrast, knockdown of key genes essential for autophagy such as Atg7 has no effect on neuronal proteasomal activity in vitro and in vivo [38,39], but polyubiquitinated proteins accumulated in autophagy-deficient neurons as inclusion bodies [39], suggesting autophagy inhibition impaired the UPS function [38]. The accumulated ubiquitin-binding proteins such as p62 may be the culprit for this effect [3,34,38]. Our study found that pharmacological and genetic inhibition of autophagy in 3T3-L1 adipocytes reduced proteasome activity and promoted expressions of GFPu and total protein ubiquitination (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast, knockdown of key genes essential for autophagy such as Atg7 has no effect on neuronal proteasomal activity in vitro and in vivo [38,39], but polyubiquitinated proteins accumulated in autophagy-deficient neurons as inclusion bodies [39], suggesting autophagy inhibition impaired the UPS function [38]. The accumulated ubiquitin-binding proteins such as p62 may be the culprit for this effect [3,34,38]. Our study found that pharmacological and genetic inhibition of autophagy in 3T3-L1 adipocytes reduced proteasome activity and promoted expressions of GFPu and total protein ubiquitination (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…1A) and increased chymotrypsin-like proteasome activity (Fig. 1B) indicate that the UPS was activated by serum star- actions between these two degradation systems [3]. Traditionally, autophagy breaks down the unnecessary or dysfunctional cellular components through lysosomal degradation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important for a polypeptide to attain and maintain its native conformation. The native conformation that a protein acquires during its biogenesis is attained through folding of the polypeptide chain spontaneously or with the help of molecular chaperones (1). However, the biogenesis of native proteins is not a very efficient process because studies have shown that approximately one third of newly synthesized polypeptides never make to mature proteins; they are cotranslationally degraded presumably due to errors in translation and/or folding (2).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, UPS impairment results in compensatory activation of autophagy for clearing damaged proteins (19)(20)(21), whereas autophagy malfunction may impair UPS performance (22,23). The function and regulation of the UPS and the ALP as well as their interplay in cardiac diseases have been recently reviewed (1,5,7). Herein we will summarize the latest literature regarding an emerging role of Nuclear factor erythroid-2 related factor 2 (Nrf2) in the regulation of intracellular PQC as well as its potential involvement in cardiac pathology.…”
Section: Introductionmentioning
confidence: 99%